KEBIJAKAN AKUNTANSI DAN PERUBAHAN ESTIMASI AKUNTANSI BERDASARKAN IFRS - Sururi . (Akademi Akuntansi YKPN Yogyakarta, 2012)
Comparability of financial statements, either in term of the multi-periods of the same entity or in term of the similar period among the similar entities in the industry, is one of the main issue in the preparation of financial statements, therefore consistency in the adoption of accounting policy and accounting estimate become the main requirement in the preparation of financial statements. Howerver, this requirement would not be able to guarantee the comparability of the statements when the accounting standard still offering a wide range of accounting alternatives. IASB has taken a big jump to narrow the accounting alternatives in order to improve the quality of financial statements in term of their comparability.Keywords: comparability, financial statements, consistency, accounting policy, accounting estimate, accounting standard.